A first look at the ability to use genomic prediction for improving the ratooning ability of sugarcane - Islam, Md. Sariful; Corak, Keo; McCord, Per; Hulse-Kemp, Amanda M.; Lipka, Alexander E. (Frontiers in Plant Science, 2023)
Sugarcane ratooning ability (RA) is the most important target trait for breeders seeking to enhance the profitability of sugarcane production by reducing the planting cost. Understanding the genetics governing RA could help breeders by identifying molecular markers which could be used for genomic-assisted breeding (GAB). A replicated field trial was conducted for three crop cycles (plant cane, first ratoon, and second ratoon) using 432 sugarcane clones, and used for conducting genome-wide association and genomic prediction of five sugar and yield component traits of RA. The RA traits for economic index (EI), stalk population (SP), stalk weight (SW), tons of cane per hectare (TCH), and tons of sucrose per hectare (TSH) were estimated from the yield and sugar data. A total of six putative quantitative trait loci and seven nonredundant single nucleotide polymorphic (SNP) markers were associated with all five tested RA traits and appear to be unique. Seven putative candidate genes were co-located with significant SNPs associated with five RA traits. The genomic prediction accuracies for those tested traits were moderate and ranged from 0.21 to 0.36. However, the models fitting fixed effects for the most significant associated makers for each respective trait did not give any advantages over the standard models without fixed effects. As a result of this study, more robust markers could be used in the future for clone selection in sugarcane, potentially helping resolve the genetic control of RA in sugarcane.